The Complex Researches of Structure and Functions of Antarctic Terrestrial Microbial Communities - Tashyrev, O.B. (Український антарктичний журнал, 2009)
Complex researches on studying structure and functions Antarctic microbial communities and formation of plural mechanisms of adaptation of microorganisms to extreme environmental factors of Antarctic are carried out. As model ecosystems subpolar thermostatic oases on the islands located in passages Lemejr and Penola along coast of Antarctic peninsula (a zone 30 x 60 km) are used. For the first time presence in environments of subpolar thermostatic Antarctic oases (including on vertical rocks) microorganisms, resistant to UV- radiation, antibiotics and toxic metals is shown. Obtained data testify to an opportunity of development on the basis of extremophilic microorganisms the express-indicator systems for an estimation of influence of climatic factors on functioning of Antarctic biota. With use of GIS-systems and 3D-models the integrated models of microbial communities' adaptation to extreme climatic factors are developed. Original positions about functioning ice algal-bacterial communities which apparently, play an essential role in formation of global vector streams of biogenic elements and balance of hotbed gases are formulated. Проведены комплексные исследования по изучению структуры и функций антарктических микробных ценозов и формированию множественных механизмов адаптации микроорганизмов к экстремальным факторам окружающей среды Антарктики. В качестве модельных экосистем использованы субполярные термостатированные оазисы на островах, расположенных в проливах Лемейр и Пенола вдоль побережья Антарктического полуострова (зона 30 x 60 км). Впервые показано наличие в биотопах субполярных термостатированных антарктических оазисов (в т.ч. на вертикальных скалах) микроорганизмов, резистентных к УФ излучению, антибиотикам и токсичным металлам. Полученные данные свидетельствуют о возможности создания на основе экстремофильных микроорганизмов экспресс-индикаторных систем для оценки влияния климатических факторов на функционирование антарктической биоты. С использованием GIS-систем и 3D-моделей разработаны интегрированные модели адаптации микробных ценозов к экстремальным климатическим факторам. Сформулированы основные положения о функционировании ледовых водорослево-бактериальных ценозов, которые, по-видимому, играют существенную роль в формировании глобальных векторных потоков биогенных элементов и балансе парниковых газов.Ключевые слова: структура, функция, микробные ценозы, модельные экосистемы. Проведено комплексні дослідження по вивченню структури і функцій антарктичних мікробних ценозів та формуванню множинних механізмів адаптації мікроорганізмів до екстремальних факторів антарктичного довкілля. У якості модельних екосистем використано субполярні термостатовані оазиси на островах, розташованих у протоках Лемейр та Пенола вздовж узбережжя Антарктичного півострова (зона 30 x 60 км). Вперше показано наявність у біотопах субполярних термостатованих антарктичних оазисів (у т.ч. на вертикальних скелях) мікроорганізмів, резистентних до УФ-випромінювання, антибіотиків та токсичних металів. Отримані дані свідчать про можливість створення на основі екстремофільних мікроорганізмів експрес-індикаторних систем для оцінки впливу кліматичних факторів на функціонування антарктичної біоти. З використанням GIS-систем та 3D-моделей розроблено інтегровані моделі адаптації мікробних ценозів до екстремальних кліматичних факторів. Сформульовано основні положення щодо функціонування льодових водоростево-бактеріальних ценозів, які, можливо, відіграють істотну роль у формуванні глобальних векторних потоків біогенних елементів та балансі парникових газів.